Effectiveness of Problem Based Learning Models Assisted by Worksheets on Students' Critical Thinking Ability - Budi, Sulistio; Franita, Yesi; Hendrastuti, Zuida Ratih (Journal of Instructional Mathematics, 2023)
This study aims to describe the effectiveness of the Problem Based Learning (PBL) model assisted by worksheet on the critical thinking ability of students. This quasi-experimental study employs the nonequivalent posttest-only control group design with the cluster random sampling technique. The study sample consists of students from classes VII B and VII C in one of the Public Junior High Schools in Magelang, Central Java, Indonesia. The research instruments used are learning tools in the form of worksheet and critical thinking ability tests. The results of this research are; 1) students who are taught using the PBL learning model assisted by worksheet against critical thinking ability are said to be effective by obtaining learning completion has reached 75%, 2) students who are taught using the direct learning model against critical thinking ability are said to be ineffective by obtaining learning completion has not reached 75%, 3) critical thinking ability of learners taught using the worksheet-assisted PBL model more effective than using the direct learning model. This study implies differences in students' critical thinking abilities when comparing the worksheet-assisted PBL learning model to the direct learning model. Education needs to apply appropriate learning models to develop students' critical thinking skills.